A preliminary study of Majlis Agama Islam Selangor (MAIS) roles in zakat administration of the Orang Asli community in education and economic sector : a case study in Kampung Orang Asli, Kuang / Wan Nur Asyiqin Wan Roslan - Wan Roslan, Wan Nur Asyiqin (Academy of Contemporary Islamic Studies (ACIS), 2016)
The Orang Asli education and economic is growing in line with the modernization. Population of Orang Asli that was improvised their education and economic is increased, especially at Kampung Orang Asli Kuang, Rawang, Selangor because it is located near the city. Education and economic growth increased smoothly when there are more educational and economic assistance has been given to the Orang Asli designated by the Selangor Islamic Religious Council (MAIS). This study examines the objectives of research to study the roles of Selangor Islamic Religious Council (MAIS) to ensure the education and economy of Orang Asli, Kuang community growth. This study is a qualitative research as involves of resources obtained from the library and also by interviews with the relevant authorities.